2012
DOI: 10.21836/pem20120506
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of gastric ulcers in weanling foals and the treatment with Omeprazole

Abstract: EinleitungDas Absetzen der Fohlen von der Mutterstute, das in der Regel zwischen dem fünften und dem siebten Lebensmonat erfolgt, ist mit einem mannigfaltigen Wechsel des Lebensumfeldes verbunden. Die Änderung der Haltung, die Futterumstellung sowie eine neue Gruppenkonstellation mit daraus resultierender Neugliederung des Sozialgefüges sind sowohl mit physischem als auch mit psychischem Stress verbunden, der Wegbereiter für das Entstehen von Magengeschwüren bei 561 M. Dahlkamp et al. Pferdeheilkunde 28 Pfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…The prevalence of gastric ulcers in Thoroughbred racehorses is estimated to be >80 % in the squamous mucosa [ 1 ]. In weanlings it ranges between 32 and 94 % [ 2 , 3 ]. Risk factors for gastric mucosa lesions, specifically for equine squamous gastric ulcer disease, are stall confinement, strenuous exercise, transport stress in adult horses (as reviewed by Andrews and others [ 4 ]), and the weaning process in foals [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of gastric ulcers in Thoroughbred racehorses is estimated to be >80 % in the squamous mucosa [ 1 ]. In weanlings it ranges between 32 and 94 % [ 2 , 3 ]. Risk factors for gastric mucosa lesions, specifically for equine squamous gastric ulcer disease, are stall confinement, strenuous exercise, transport stress in adult horses (as reviewed by Andrews and others [ 4 ]), and the weaning process in foals [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In weanlings it ranges between 32 and 94 % [ 2 , 3 ]. Risk factors for gastric mucosa lesions, specifically for equine squamous gastric ulcer disease, are stall confinement, strenuous exercise, transport stress in adult horses (as reviewed by Andrews and others [ 4 ]), and the weaning process in foals [ 2 , 3 ]. Nonsteroidal anti-inflammatory drugs have been demonstrated to be a risk factor for the equine glandular region in adult horses and foals [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Therapie sollte 3-4 Wochen durchgeführt werden, bevor eine gastroskopische Nachkontrolle erfolgt [6]. Die alleinige Applikation von Omeprazol bei Fohlen während des Absetzens konnte zeigen, dass zwar Läsionen der kutanen Schleimhaut eine signifikante Besserung zeigten, die glanduläre Schleimhaut hingegen signifikant mehr Ulzerationen aufwies [7], sodass die Autoren zu dem Schluss gelangten, dass eine prophylaktische Gabe von Omeprazol bei absetzbedingten Magenulzera nicht gerechtfertigt ist.…”
Section: Omeprazolunclassified
“…The prevalence of EGUS in foals ranges between 30 and 50% particularly in weanlings (Dahlkamp et al 2012). Before weaning, Dahlkamp et al (2012) found gastric ulcers in 38 out of 79 foals they examined. After weaning, the number of affected foals, as well as the severity, increased significantly.…”
Section: Introductionmentioning
confidence: 98%
“…In Canada, a study of 94 thoroughbred horses revealed EGUS in 74.5 % of the examined horses (Marques et al 2011). The prevalence of EGUS in foals ranges between 30 and 50% particularly in weanlings (Dahlkamp et al 2012). Before weaning, Dahlkamp et al (2012) found gastric ulcers in 38 out of 79 foals they examined.…”
Section: Introductionmentioning
confidence: 99%